Pesticides and environment - Singh, Balwinder, ed. (New Delhi : Commonwealth Publishers, 2000)
Environment Management
Keywords: Pesticides; Insecticide; Soil health; Food commodities; Herbicides; Fungicides; Agroecosystems; Pest management; Microbial pesticides